Cell Cycle Control of Cdc7p Kinase Activity through Regulation of Dbf4p Stability - Oshiro, Guy (American Society for Microbiology, 1999)
In Saccharomyces cerevisiae, the heteromeric kinase complex Cdc7p-Dbf4p plays a pivotal role at replication origins in triggering the initiation of DNA replication during the S phase. We have assayed the kinase activity of endogenous levels of Cdc7p kinase by using a likely physiological target, Mcm2p, as a substrate. Using this assay, we have confirmed that Cdc7p kinase activity fluctuates during the cell cycle; it is low in the G(1) phase, rises as cells enter the S phase, and remains high until cells complete mitosis. These changes in kinase activity cannot be accounted for by changes in the levels of the catalytic subunit Cdc7p, as these levels are constant during the cell cycle. However, the fluctuations in kinase activity do correlate with levels of the regulatory subunit Dbf4p. The regulation of Dbf4p levels can be attributed in part to increased degradation of the protein in G(1) cells. This G(1)-phase instability is cdc16 dependent, suggesting a role of the anaphase-promoting complex in the turnover of Dbf4p. Overexpression of Dbf4p in the G(1) phase can partially overcome this elevated turnover and lead to an increase in Cdc7p kinase activity. Thus, the regulation of Dbf4p levels through the control of Dbf4p degradation has an important role in the regulation of Cdc7p kinase activity during the cell cycle.